SCIENCE OF SALAT MOVEMENT IN COVID-19 ERA AND TURBULENCE ECONOMIC - R Mochamad A (Jurnal As-Salam, 2020)
Abstract: This study aims to analyze the salat movements associated with Covid-19 and economic turbulence. The secret in the salat movement gives health to the human body. By continuing to carry out the obligation of salat as a Muslim, and the current economic condition shaken by Covid-19, could become one of the strongholds of economic turbulence. Data is taken from content in the form of stages of ablution and salat movement, secondary data obtained from the Central Bureau of Statistics (BPS), World Health Organization (WHO), International Monetary Fund (IMF), and Worldbank. This study uses a content analysis methodology, with a Hahslm theory approach that integrates Covid-19, Islamic economics and religiosity and the Koran. The results show that health, patience and religiosity can strengthen the resilience of Covid-19 as well as by offering salat to face the economic crisis. Keywords: Islam, Health, Salat Movement, Covid-19, Economy Abstrak: Penelitian ini bertujuan untuk menganalisis gerakan sholat yang berkaitan dengan Covid-19 serta turbulensi ekonomi. Rahasia dalam gerakan shalat memberikan kesehatan bagi tubuh manusia. Dengan tetap menjalankan kewajiban salat sebagai seorang umat Islam, dan keaadan ekonomi saat ini yang tergunvang oleh Covid-19 bisa menjadi salah satu benteng pertahanan terhadap turbelensi ekonomi. Data diambil dari konten berupa tahapan wudu dan gerakan salat, data sekunder diperoleh dari Biro Pusat Statistik (BPS), World Health Organization (WHO), International Monetary Fund (IMF), dan Worldbank. Studi ini menggunakan metodologi analisis konten, dengan pendekatan teori Hahslm yang mengintegrasikan Covid-19, ekonomi dan religiusitas Islam dan Al-Quran. Hasil menunjukkan bahwa kesehatan, kesabaran, dan religiusitas dapat memperkuat ketahanan diri dari Covid-19 serta dengan salat untuk menghadapi krisis ekonomi. Kata-kata kunci: Islam, Kesehatan, Gerakan Shalat, Covid-19, Ekonomi